PENGARUH DISOVERY LEARNING BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR SISWA BROADCASTING DAN PERFILMAN - Ayu Sarwendah (Fitrah, 2023)
This study aims to analyze the effect of the wordwall-assisted Discovery learning towards student’s learning outcomes in the Broadcasting and Film major at SMK Negeri 2 Kota Kediri. This study used a quantitative approach with a quasi-experimental research type, that had an experimental class taught using a wordwall-assisted Discovery learning and a control class taught using a conventional learning. The design of this study was a posttest only with non-equivalent control group design. The results showed that there were differences in student learning outcomes between the experimental class and the control class with a significance value of 0.000 <0.005. The average value of the experimental class was 84.53 with a minimum value of 80 and a maximum of 92. Meanwhile, the average value of the control class was 77.65 with a minimum value of 60 and a maximum of 84. Therefore it can be concluded that there is an effect of the wordwall-assisted Discovery learning toward student’s learning outcomes in the Broadcasting and Film major at SMK Negeri 2 Kota Kediri. It is hoped that the results of this study can improve and train teacher skills and mastery in managing learning with the wordwall-assisted Discovery learning so that it can be developed in other materials.